The partnership co-creation process: Conditions for success? - Smith, Susan; Akhyani, Kimiya; Axson, Dan; Arnautu, Andre; Stanimirova, Ilina (International Journal for Students as Partners, 2021)
Staff-student partnership activity continues to increase across the higher education sector, expanding to encompass a broad range of initiatives. Numerous frameworks and typologies have been proposed to help organise the literature and facilitate comparisons among different types of partnerships. The research reported here draws on a case study of a quality-enhancement staff-student partnership to identify the stages of the partnership co-creation process. It argues that the establishment of partnership values is intertwined with the stages of the co-creation process and is critical to the partnership’s success. This research contributes to practice and the literature by offering a practical approach to managing a staff-student partnership, adding to work on quality enhancement partnerships, and extending prior work evaluating partnership activity from the perspectives of multiple stakeholders.